Psychological restraint in captive Sumatran rhinoceros (Dicerorhinus sumatrensis) - Zainuddin, Zainal-Zahari (Department of Wildlife and National Parks - Perhilitan, 1989)
Proper captive management includes an appropriate handling and restraint technique. Psychological restraint requires little or no use of equipment unlike physical restraint. This method was successful in 12 Sumatran rhinoceros Dicerorhinus sumatrensis of varying ages. Stimulation of the errogenous zones near the prepubis resulted in the animal going into a dog sitting position and subsequent lateral recumbency.